Antioxidant and cytotoxic agent from the rhizomes of Kaempferia pandurata - Mulyadi Tanjung (Elsevier, 2013)
Objective:To determine antioxidant and cytotoxic activity of two flavanones, pinocembrin (1) and pinostrobin (2) from the rhizomes of Kaempferia pandurata. The chemical structures of both compounds were determined based on spectroscopic data, including UV, IR, MS and NMR spectra. Methods:The antioxidant activities of pinocembrin (1) and pinostrobin (2) were assayed by using 2,2-diphenyl-1-picrylhydrazyl. Cytotoxic assay was done by using brine shrimp lethality test,and cytotoxic properties was tested against murine leukemia P-388 cells. Results:Compounds 1-2 were evaluated for their antioxidant properties against DPPH, showingtheirIC50 were 5 816 and 6 268µ mol/L; brine shrimp lethality test: LC 50 23.3 and 60.5 µ g/mL; murine leukemia P-388: IC 50 176.3 and 218.5 µ mol/L. Conclutions:The results indicated that pinocembrin (1) was slightly more active than pinostrobin (2).